Labour market institutions and labour market performance : a survey of the literature - Arpaia, Alfonso; Mourre, Gilles; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2005)
This paper presents a selective survey of the recent literature on labour market institutions. It describes the different empirical approaches used to explore the nexus between labour market institutions and labour market performance. It stresses that the effect of institutions is complex in both stock and flow models and that it is also crucial to take into account the interactions they generate among themselves and with macroeconomic shocks.
Economic Papers